(untitled) (Fiep Bulletin - online, 2011)
This study aims to identify the social representations of ’being an immigrant’ and ’health service’ able to interfere with quality of life. It’s about an exploratory study that seeks to explore the phenomenon of migration in diverse aspects, emphasizing psicosócio-cultural aspects from social representations for immigrants. Points out the knowledge, images, attitudes and beliefs in the daily broadcast collectively performed with twelve Portuguese immigrants living in João Pessoa-PB, of both sexes. To collect data we used an in-depth interview and the test of free association of words, with the stimulus inductors: access to health services and being an immigrant, previously scheduled with an average of thirty minutes for each participant. The data obtained from interviews were analyzed using the technique of thematic content analysis and then were submitted to software Alceste. The data seized from Alceste pointed to five broad categories that are interpreted subsidized in the theory of social representations.